Knowledge, attitude and practice towards HIV post-exposure prophylaxis of health professionals of Gimbi town in Ethiopia: a cross-sectional study - Tesfaye, Gurmu; Gebeyehu, Habte; Likisa, Jimma (International Journal of Research in Medical Sciences, 2017)
Background:According to World Health Organization (WHO) estimation, about 2.5% of all human immunodeficiency virus (HIV) cases among health workers worldwide are due to the result of exposures to risky conditions. Post exposure prophylaxis (PEP) treatment has been shown to reduce the risk of HIV infection significantly if administered shortly following exposure. However, it has been shown that there is knowledge gap, lower degree of utilization and limited acceptance rate of the method by health care workers (HCWs) in resource limited settings. Therefore, this study aimed at assessing the knowledge, attitude and practice of HIV PEP use among health care workers of Gimbi hospital and Gimbi health center in Ethiopia. Methods: Facility based descriptive cross-sectional study was undertaken from February, 1 - 30, 2013. Pretested structured questionnaires were used for data collection. SPSS version 20.0 was used to analysis data. Chi-square (X2) was employed to assess association between knowledge, attitude and practice of PEP following HIV. Results:In this study, all of the study subjects heard about HIV PEP. More than half of them (54.2%) could correctly identify the drugs used for HIV PEP. While, 60 (83.3%) of the study subjects had positive attitude toward PEP use. Half of the study subjects had ever been exposed to HIV risk condition of whom only 6 (16.7%) had ever used PEP. No association had been obtained among knowledge, attitude and practice of the study subjects. Conclusion: In this study very low rate of PEP utilization up on exposure to HIV risk conditions was seen even though the significant proportion of these professionals had adequate knowledge and positive attitude toward PEP. Much work had to be done by policy makers to increase the uptake of the method by health care workers to mitigate the rising epidemic of HIV/AIDS in the country.